EVALUATION OF COMPARATIVE ACADEMIC PERFORMANCE OF UNDERGRADUATE STUDENTS AT UNIVERSITY LEVEL - B. B. Khan; R. Nawaz; K. M. Chaudhry A. U. Hyder; T. M. Butt (Journal of Animal and Plant Sciences, 2012)
The study was undertaken to evaluate the comparative academic performance of male and female students, day scholars and boarders and of rural and urban area students at undergraduate level in the University of Agriculture, Faisalabad (UAF). In all, 265 students responded to a pretested questionnaire. Of these, 96 were females. The evaluation of performance was based on GPA and CGPA obtained by students in various groups in their first and sixth semester respectively. In “above 3.00 GPA” category, less than 50% male students were placed, whereas almost 60% females attained this level in first semester. When CGPA in sixth semester in “above 3.00” category was compared, 28% more females earned higher than 3.00 CGPA, showing thereby better performance of females than their counterparts. The comparative academic performance of dayscholars and boarders was almost of the same level in first and sixth semesters, with no significant difference between the two groups. The comparison of educational performance between rural and urban students at different levels of GPA and CGPA in first and sixth semester respectively exhibited varying and mixed trends in results.
Keywords: Academic performance; dayscholars; boarders; rural; urban